Developing Early Childhood Character through the Storytelling Method of Prophet Moses - afif rahman; Dwi Wanda Umami; Firdha Hayati (Universitas muhammadiyah Banjarmasin, 2023)
Lately, we have encountered a lot of character decline, such as a lack of understanding of courtesy to parents. This is of great concern to early childhood educators because character values should be instilled from an early age so that good character is realized in accordance with the values adopted by the Indonesian nation. This research is a qualitative descriptive study with 14 children in Kindergarten B at the Bina Insan Sejahtera School, Banjarmasin as subjects. Researchers collected data using the method of observation, interviews with the teacher concerned and documentation. The results of this study are, with the method of telling the story of Prophet Musa AS, it can develop AUD characters. This can be seen that children have good character in terms of character and good morals.